Literature Review: Effectiveness of Digital Self-Reporting on Tuberculosis Treatment Completion Adherence - Gustini Putri Dewanti; Masfuri Masfuri (Journal of Nursing Care, 2023)
Tuberculosis (TB) is a directly infectious disease caused by Mycobacterium tuberculosis. Medication adherence important to recovery TB patients. Failure of TB medication can caused spreading infection, MDR-TB (Multi Drug Resistant) to  mortality. Digital based for self-reporting can help to improve medication adherence. Purpose: To determine the effectiveness of digital based self reporting that can encourage medication adherence in TB medication.  Methods: Scooping  review of international article with the keywords “digital health”, “tuberculosis”, “medical adherence” through the online database Scopus and Clinical Key with inclusion criteria : digital health for TB patient, SMS, VDOT, and 99DOTS use in TB medication, and article published between 2017-2022. Study did in October – December 2022 to analyze assosiated based self reporting that can encourage medication adherence in TB medication  The result, a Analysis related to intervention using 99DOTS and SMS showing increased significant and unsignificant.  VDOT shows increasing in TB adherence medication so that it can be recommended for apply.: Digital based self reporting that can encourage medication adherence in TB medication.